2021
DOI: 10.1186/s12889-021-11452-x
|View full text |Cite|
|
Sign up to set email alerts
|

Building on existing tools to improve chronic disease prevention and screening in public health: a cluster randomized trial

Abstract: Background The BETTER (Building on Existing Tools to Improve Chronic Disease Prevention and Screening in Primary Care) intervention was designed to integrate the approach to chronic disease prevention and screening in primary care and demonstrated effective in a previous randomized trial. Methods We tested the effectiveness of the BETTER HEALTH intervention, a public health adaptation of BETTER, at improving participation in chronic disease prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
9
2
Order By: Relevance
“…The primary results from BETTER WISE have now been published. In contrast to previous BETTER programme studies mentioned above,15–17 the primary intention-to-treat (ITT) analyses, which did not consider financial difficulty, show that the effectiveness of the BETTER WISE intervention was not statistically significant, although per-protocol analyses of participants enrolled prior to the imposition of the COVID-19 restrictions showed a 21% improvement (p=0.001) in CCDPS compared with usual care 19…”
Section: Introductioncontrasting
confidence: 57%
“…The primary results from BETTER WISE have now been published. In contrast to previous BETTER programme studies mentioned above,15–17 the primary intention-to-treat (ITT) analyses, which did not consider financial difficulty, show that the effectiveness of the BETTER WISE intervention was not statistically significant, although per-protocol analyses of participants enrolled prior to the imposition of the COVID-19 restrictions showed a 21% improvement (p=0.001) in CCDPS compared with usual care 19…”
Section: Introductioncontrasting
confidence: 57%
“…Initiated by the 1995 Institute of Medicine report Setting Priorities for Clinical Practice Guidelines [ 30 ], several decades of investment have resulted in robust methods to create high-quality guidelines; however, to achieve intended outcomes, CPGs must be implementable in real-world practice. The BETTER program has demonstrated that nuanced clinical tools can be designed to facilitate decision-making between PCPs and patients across multiple chronic diseases and lifestyle factors [ 2 , 17 , 18 ]. In this evidence review, we extended our topic scope, included health policy makers and patients in the evidence synthesis process, and tailored the included clinical recommendations for implementation in 4 Canadian provinces.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence-based prevention prescription is rooted in harmonized, high-quality CCDPS guidelines and tailored to patients based on their medical history, risk factors, and family history. This cost-effective intervention has been demonstrated to improve uptake of CCDPS actions in urban primary care settings as compared to usual care [ 2 ] and similar improvements have been observed in rural and remote communities [ 17 ] and public health settings [ 18 ] across Canada.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, in the original BETTER trial, about half of the participants had an income of $100,000 (CAD) or higher [ 7 ]. Since a large number of Canadians do not have access to a primary care practitioner [ 12 ] and it was unknown if the BETTER intervention would be effective for people living with low income, we adapted the BETTER intervention to a public health setting (without access to electronic or paper medical records from any source) with public health nurses as PPs, and conducted a cluster randomized controlled trial (cRCT) that compared the adapted BETTER intervention to a wait-list control [ 13 , 14 ]. We previously reported that six months after the prevention visit participants in the intervention arm met 64.5% of actions for which they were eligible versus 42.1% in the wait-list arm (rate ratio 1.53 [95% confidence interval 1.22–1.84]) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%